(untitled) (Research Bulletins of the Faculty of Economic Sciences, 2018)
The pharmaceutical market is a specific market, because it has its own rules, which distinguishes it from other sectors of health services. This area of health services operates on the basis of a market mechanism, but with a strong emphasis on compliance with legal regulations. There is a competition between manufacturers, wholesalers and pharmacies, while the state plays the role of a moderator regulating the functioning of the entire system. The functioning of the management system for this specific area is still imperfect. This article presents the specifics of the pharmaceutical market, behaviors of patients as well as the results of the conducted researches.